2016
DOI: 10.1007/s10236-016-0963-x
|View full text |Cite
|
Sign up to set email alerts
|

Surface wave effects on water temperature in the Baltic Sea: simulations with the coupled NEMO-WAM model

Abstract: Coupled circulation (NEMO) and wave model (WAM) system was used to study the effects of surface ocean waves on water temperature distribution and heat exchange at regional scale (the Baltic Sea). Four scenarios-including Stokes-Coriolis force, sea-state dependent energy flux (additional turbulent kinetic energy due to breaking waves), seastate dependent momentum flux and the combination these forcings-were simulated to test the impact of different terms on simulated temperature distribution. The scenario simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 57 publications
7
67
0
Order By: Relevance
“…Locations of the buoys shown in Fig. 1 percentiles were of the same magnitude reported by Alari et al (2016) in moderate storms. The maximum speed of the surface Stokes drift had large spatial variability (not shown).…”
Section: Annual Stokes Drift Statisticssupporting
confidence: 61%
See 1 more Smart Citation
“…Locations of the buoys shown in Fig. 1 percentiles were of the same magnitude reported by Alari et al (2016) in moderate storms. The maximum speed of the surface Stokes drift had large spatial variability (not shown).…”
Section: Annual Stokes Drift Statisticssupporting
confidence: 61%
“…Previously, Alari et al (2016) have evaluated the importance of surface wave effects in the sea surface layer and identified that even in moderate storms, the surface Stokes drift can reach up to 0.35 ms −1 . Here, we calculated the surface Stokes drift for the entire Baltic Sea with the wave model WAM and gave mean values and percentiles of the Stokes drift speed from a 10-year model simulation (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015).…”
Section: Introductionmentioning
confidence: 99%
“…Surface Stokes drift is normally obtained from a wave model (or by any Reader), and its decline with depth is calculated as described in Breivik et al (2016).…”
Section: Openoil (Oil Drift)mentioning
confidence: 99%
“…All objects are assumed to be small enough that direct wave scattering forces are insignificant. Furthermore, the Stokes drift (Kenyon, 1969;Breivik et al, 2014Breivik et al, , 2016) is inherently part of the leeway obtained from observations. As wind-generated waves have a mean direction closely aligned with the local wind direction it is neither practical nor desirable to disentangle the Stokes drift from the wind drag for leeway simulations.…”
mentioning
confidence: 99%
“…The additional terms accounting for wave-current interaction that are considered in this study are the Stokes-Coriolis force (Breivik et al 2014) the sea-state-dependent energy and wave-modulated momentum fluxes. The same regional model setup with forcing from a WAM wave model has previously been described by Alari et al (2016) where the focus was the influence of wave effects on surface water temperature. The individual and collective role of these processes is quantified and the results are compared with a control run without wave effects as well as against current and water-level measurements from coastal stations.…”
Section: The 14th Workhopmentioning
confidence: 99%